Leader humility and constructive voice behavior in China: a dual process model. Issue 6 (3rd September 2018) - Li, Jie; Liang, Qiaozhuan; Zhang, Zhenzhen; Wang, Xiao
Abstract : Purpose: The purpose of this paper is to find how leader humility affects employees' constructive voice behavior toward supervisor (speaking up) and coworkers (speaking out) from an identification-based perspective, and seeks to verify the effectiveness of leader humility in the Chinese context. Design/methodology/approach: Data were collected from 325 employees in four Chinese companies with two phases. In the first phase, the participants were asked to report the leader humility, their identification of their relations with the supervisor, and their identification with their organization. In the second phase, they were asked to report their voice behaviors toward their supervisors and coworkers. Findings: The results indicate that leader humility strongly predicts both employees' voice behaviors of speaking up and speaking out. Results further suggest that relational identification with the supervisor explains why leader humility promotes employees speaking up, while organizational identification explains why leader humility promotes employees speaking up and speaking out. Practical implications: Managers with humility can successfully shape employees' relational and organizational identifications, which in turn encourage their voice behaviors toward supervisors and coworkers. Hence, behaving humbly in working places could be an effective way for managers to promote organizational cohesion and creativity. Originality/value: Although leader humility attracts much attention in both academia and practice, researchers have been primarily focusing on conceptual development and measurement issues, and empirical studies are rare. This is the first research connecting leader humility and employee proactive behaviors. Moreover, it takes an in-depth analysis of the constructive voice behaviors by differentiating them based on their targets.